2007
DOI: 10.1197/j.aem.2006.10.094
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Effects of Intravenous Fat Emulsion in an Animal Model of Severe Verapamil Toxicity Resuscitated with Atropine, Calcium, and Saline

Abstract: Standard resuscitation and IFE increase MAP and survival in an animal model of severe verapamil toxicity compared with standard resuscitation alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(25 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…16 The 'lipid sink' theory might conceptually be applied to any lipophilic toxin. Consistent with this, ILE has been trialled in animal models of amitriptyline, 17 atenolol, 18 bupivacaine, 5,6 chlorpromazine, 12 clomipramine, 15,19 metoprolol, 20 organophosphate pesticide, 21 propranolol 22,23 and verapamil 16,24 with variable outcome. A number of recent reviews summarizing the animal work in this area [25][26][27] have found repeatable large effects, dose responsiveness and mechanistic evidence of the biologic plausibility for ILE as an antidote for lipophilic toxins.…”
Section: Introductionmentioning
confidence: 84%
“…16 The 'lipid sink' theory might conceptually be applied to any lipophilic toxin. Consistent with this, ILE has been trialled in animal models of amitriptyline, 17 atenolol, 18 bupivacaine, 5,6 chlorpromazine, 12 clomipramine, 15,19 metoprolol, 20 organophosphate pesticide, 21 propranolol 22,23 and verapamil 16,24 with variable outcome. A number of recent reviews summarizing the animal work in this area [25][26][27] have found repeatable large effects, dose responsiveness and mechanistic evidence of the biologic plausibility for ILE as an antidote for lipophilic toxins.…”
Section: Introductionmentioning
confidence: 84%
“…9 Although no prospective clinical trials are available to critically assess efficacy, there are multiple animal experimental models and human case reports that support these treatment interven-tions over previous traditional therapies (eg, glucagon, vasopressors). 7,9,11,12,16,18 The use of ILE, also known as intravenous fat emulsion and "lipid therapy," has been shown to be a potentially effective therapy for fat-soluble toxins. 8,10 Research in animal models along with human and veterinary case reports have described variable success in clinical improvement from fat-soluble toxicoses.…”
Section: Discussionmentioning
confidence: 99%
“…8,10 Research in animal models along with human and veterinary case reports have described variable success in clinical improvement from fat-soluble toxicoses. 8,11,12,[26][27][28] Current considerations in both human and veterinary medicine for the use of ILE include overdoses of local anesthetics (eg, lidocaine, bupivacaine, etc. ), antidepressants (eg, lamotrigine), beta blockers, CCBs, macrocytic lactones (eg, ivermectin, milbemycin, moxidectin), and muscle relaxants (eg, baclofen).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41,42 Intravenous Lipid Emulsion Therapy CCBs are naturally lipophilic, and intravenous lipid emulsion (ILE) therapy has been attempted with success in cases of severe CCB overdose. 43,44 A systematic review by Jamaty et al 45 showed that, although the overall quality of the evidence for this modality was poor, ILE could be beneficial in the management of severe cases of CCB poisoning. ILE therapy was first described by Weinberg et al for bupivacaine toxicity in the year 2003.…”
Section: Titration Of the Insulin Infusion Is Usually To The Resolutimentioning
confidence: 99%